2002
DOI: 10.1111/1536-7150.00169
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Impact of State Abortion Restrictions

Abstract: This paper shows that a state's abortion policy is determined by the strength of interest advocacy groups and political forces. The greater the membership in the National Abortion Rights Action League, the percentage of female state legislators and the percentage of Democratic female legislators, the less restrictive a state's abortion policy. The greater a state's population that are Roman Catholics, the more restrictive a state's abortion policy. The paper also estimates the impact abortion restrictions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…Building off theories of critical mass, several scholars find that as the presence of women legislators increases, the adoption of restrictive abortion policy is less likely. These findings are stronger when looking at only Democratic women (Hansen 1993;Medoff 2002;Norrander and Wilcox 2001;Tatalovich and Schier 1993). However, these findings are not universal.…”
Section: Descriptive and Partisan Representationmentioning
confidence: 94%
“…Building off theories of critical mass, several scholars find that as the presence of women legislators increases, the adoption of restrictive abortion policy is less likely. These findings are stronger when looking at only Democratic women (Hansen 1993;Medoff 2002;Norrander and Wilcox 2001;Tatalovich and Schier 1993). However, these findings are not universal.…”
Section: Descriptive and Partisan Representationmentioning
confidence: 94%
“…(1) was greater than .25. In addition, both Cohen and Barrilleaux (1993) and Medoff (2002) found that a state's passage of restrictive abortion laws was not a reaction to a state's abortion rates. Each of these studies found that a state's restrictive abortion policy was a function of the political strength of well-organized and highly mobilized interest groups opposed to abortion.…”
Section: Methodsmentioning
confidence: 99%
“…The partial derivative on the left indicates that raising the cost of abortion via reducing abortion subsidies or restricting its access (physically or legally) reduces the gains associated with it [16]. If either action is such that the gain to a PS mother who is faced with time limits is negative  , property (10) holds.…”
Section: Other Policy Effectsmentioning
confidence: 99%